ANALISIS RISIKO SAHAM PERUSAHAAN ANEKA INDUSTRI DI BURSA EFEK INDONESIA - Mahrina Sari; Khaira Amalia Fachrudin (Universitas Sumatera Utara, 2013)
ABSTRACT This study aims to identify and analyze the differences in systematic risk and unsystematic risk in the Automotive Components sub-sector, sub-sector of Textile and Garment, Footwear sub-sector, sub-sector of Cables, and Electronics subsector in Indonesia Stock Exchange. This research is a comparative study using a quantitative approach. Total population in this study are 35 companies included in the Miscellaneous Industry Sector in Indonesia Stock Exchange. Data obtained by collecting secondary data reports daily stock price on January 1, 2012 until December 31, 2012. The analysis method that is done using analysis of One Way ANOVA test with a significance level of 5%. One Way ANOVA test results showed that there is no difference in systematic risk and unsystematic risk in the Automotive and Components sub-sector, subsector Textile and Garments, Footwear sub sector, subsector Cables and Electronics sub-sector in Indonesia Stock Exchange. Keywords: Systematic Risk, Unsystematic Risk, Miscellaneous Industry